Mechanistic insights into GPAA1-mediated cold tumor phenotype and immune evasion in colorectal cancer: integrative multi-omics analysis and experimental validation - Zhu, Jia; Zhu, Tao; Cai, Yichen; Fan, Hancheng (Frontiers in Oncology, 2025)
BackgroundGlycosylphosphatidylinositol(GPI) Anchor Attachment Protein 1 (GPAA1) plays a critical role in GPI-anchor biosynthesis, yet its pan-cancer expression patterns and functional significance in Colorectal Cancer(CRC) remain unclear.MethodsWe integrated multi-omics data (TCGA, GTEx, GEO, HPA) to analyze GPAA1 expression, immune infiltration, and genomic instability in CRC. Single-cell/spatial transcriptomics and functional assays (proliferation, migration, invasion) were performed to validate findings.ResultsGPAA1 was significantly overexpressed in CRC (mRNA and protein, p < 0.05) and associated with poor prognosis. High GPAA1 correlated with genomic instability (aneuploidy, HRD) and an immune-cold phenotype (reduced CD8+ T cells, increased M2 macrophages). Functional assays confirmed GPAA1 promotes CRC aggressiveness.ConclusionGPAA1 drives CRC progression via genomic instability and immunosuppression, serving as a prognostic biomarker and potential therapeutic target.